The Myth of Inanna and Bilulu - Jacobsen, Thorkild
1. Form and Affinities — 2. Story — 3. Mythological Interpretation — 4. Possibilities of Appreciation — 5. Transliteration — 6. Appendix: A Note by S. N. Kramer.